2015
DOI: 10.1111/aogs.12577
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intraperitoneal chemotherapy for the treatment of recurrent ovarian cancer in elderly women

Abstract: Our aim was to evaluate the morbidity and survival associated with combined cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) in the treatment of recurrent ovarian cancer for patients aged 70 years and older. We conducted a monocentric study in a French university hospital and collected data on 15 women aged ≥ 70 years, treated by cytoreduction and HIPEC for ovarian cancer relapse. The median overall survival was 35 months, with a median disease-free survival of 15.6 months. When a Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…In patients with advanced disease, nearly 85% will relapse even after adequate initial treatment ( 57 ). In these cases, treatment usually involves follow-up chemotherapy, avoiding surgery and surgery-related morbidities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with advanced disease, nearly 85% will relapse even after adequate initial treatment ( 57 ). In these cases, treatment usually involves follow-up chemotherapy, avoiding surgery and surgery-related morbidities.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, treatment usually involves follow-up chemotherapy, avoiding surgery and surgery-related morbidities. To address this problem, a small study examined cytoreductive surgery and HIPEC in elderly women ( 57 ). No patients died immediately after surgery or from HIPEC-related complications.…”
Section: Methodsmentioning
confidence: 99%
“…Ceelen et al 73 77 (15.6 months). It is also of note that, after a median follow-up of 16 months (range, 5Y23 months) and 32 months (range, 25-56 months), Argenta et al 55 and Gouy et al, 56 respectively, reported DFS rates of 70% and 28.6%.…”
Section: Disease-free Survivalmentioning
confidence: 98%
“…In the largest multicenter study, 76 with N = 474 patients, cisplatin was the most commonly used agent (75%) either on its own or in combination with mitomycin or doxorubicin. Five studies 77Y81 used cisplatin with doxorubicin, 77,79,80 paclitaxel, 78 or mitomycin. 79Y81 Three studies used oxaliplatin, 56,72,73 with only 1 study electing to use it in combination (with irinotecan in some patients).…”
Section: Choice Of Hipec Drugs/regimenmentioning
confidence: 99%
“…The HIPEC chemotherapy used, temperature and duration was described in all 37 studies (eTable 2). The most commonly used HIPEC chemotherapy was cisplatin (CDDP) that was used either alone [26,42,49,50,55], or in combination with other agents such as doxorubicin [36,37,41,45,56], paclitaxel [40] or mitomycin-C [34,57] Figure 1). Only one study reached median overall survival for CRS with and without HIPEC (64.4 months and 46.4, respectively).…”
Section: Study Characteristicsmentioning
confidence: 99%